ANALISIS MAKNA VISUAL POSTER FILM JUJUTSU KAISEN 0 - Citra Agustina; Fajar Persada Supandi (Puslitabmas Batam Tourism Polytecnic, 2024)
Film poster is one of the visual promotional media as the identity of the movie that will be shown. Film posters are made by showing information that contains visual elements and verbal elements that make it attractive to the audience and contain implied meanings such as one example is the poster of the movie Jujutsu Kaisen 0. The purpose of this research is to study the semiotics contained in the Jujutsu Kaisen 0 poster along with the denotation and connotation meanings. The research method used in this study is a qualitative method with an analysis method using online observation and with a semiotic approach that provides an explanation of the visual meaning contained in the Jujutsu Kaisen 0 movie. This research was conducted by explaining the existing visual meaning and visual elements with the theory contained in the movie poster. The result of this research is to understand the semiotic meaning of the visual elements and verbal elements in the movie Jujutsu Kaisen 0. This research shows that there is a semiotic meaning in the visual elements and verbal elements of the poster that has an implied meaning related to the storyline of the movie from Jujutsu Kaisen 0.